Resposta de cultivares de feijão comum à adubação nitrogenada - Aires, Bruno Corrêa [UNESP] (2014)
The search of new and more productive common bean cultivars, w ith lower production cost s and adapted to new cropping systems has been increased . Aiming higher grain yield, supply the common bean crop with nitrogen (N) is critical due to be the nutrient which is uptaken in largest amounts by common bean , and because a bou t 50% of the total N absorbed is exported by the grain, its deficiency is the most observed . Nevertheless, lack of information about the demand for this nutrient by new cultivars is frequent , as well as the response of these cultivars to N fertilization . Thus, it was aimed to evaluate the response of recently launched to the market common bean cultivars to N rates. Hence , two experiments were carried out in 2013, during the “ drought and rainy growing seasons. The experiment s were carried out in a clay ey - textured red dystrophic Nitosol , in Botucatu - SP. The experiment was in a randomized complete block design , in a 7 x 4 factorial scheme , with four replications. The treatments were a combination of seven carioca - type common bean cultivars (Pérola, BRS Am e tista, BRS Notável, IPR Campos G erais, IPR Tangará, IAC Formoso , and IAC Imperador) and four N rates (0, 35, 70 , and 140 kg ha - 1 ), applied at top dressing ( stage V 4 ), using ammonium nitrate as the source . Regardless of N rate , the cultivars BRS Notável and IAC Imperador presented earlier flowering and shorter cycle than the others. The se cultivars showed different relative chlorophyll index in leaves, as well as different response of this variable as to N fertilization, but , in general, the N rates increase d the relative chlorophyll index of common bean cultivars. The cultivars responses to N fertilization differed depending on the growing season. In the dr ought growing season , with warmer weather in the vegetative stage, the Pérola and IPR Campos Gerais s howed reduction on grain ...